1997
DOI: 10.1111/j.1745-493x.1997.tb00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplier Selection Decisions In Systems/Software Purchases

Abstract: Changing business conditions are likely to influence the supplier evaluation process and, thus, the relevance of selection criteria should be periodically reconsidered. In order to explore this issue, an empirical study of logistics executives' perceptions of the relative importance of specific criteria (used in the selection of systems/software vendors) was conducted. The respondents identified vendor attributes (i.e., support, reliability) and product/service attributes (i.e., flexibility, ease of use) to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…'Lower prices' is the most frequently cited reason for pursuing a purchasing strategy, and price has been an important determinant of the purchasing decision process (Gustin et al, 1997). Consistent with the earlier work of Lehmann and O'Shaughnessy (1974), Evans (1994) described price as a top priority and the most important attribute during the implementation of a purchasing strategic plan concerning purchases of routine products.…”
Section: Competitive Pricingmentioning
confidence: 90%
See 2 more Smart Citations
“…'Lower prices' is the most frequently cited reason for pursuing a purchasing strategy, and price has been an important determinant of the purchasing decision process (Gustin et al, 1997). Consistent with the earlier work of Lehmann and O'Shaughnessy (1974), Evans (1994) described price as a top priority and the most important attribute during the implementation of a purchasing strategic plan concerning purchases of routine products.…”
Section: Competitive Pricingmentioning
confidence: 90%
“…Modern purchasing processes include auditing the potential suppliers' strategic capabilities, such as their ability to contribute to future product development (Monczka, Callahan & Nichols, 1995). Recently, Gustin et al (1997) stress the importance of supplier efficiency as one of the most highly rated purchasing criteria. Buyers are aware of the need for a long-term interactive relationship with a vendor, and the possession of such capabilities by the supplier is essential for the buyer's attempt to gain competitive advantage.…”
Section: Technological Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Gustin et al [8], flexibility and ease of use were identified as the most important criteria used in the selection of contractors to supply an Integrated Logistics Information system. Whilst cost was considered moderately important, it appeared that operability and adaptability were of primary importance under this scenario.…”
Section: Introductionmentioning
confidence: 99%
“…They will each have to be managed, maintained and operated internally. A summary of these factors based on the literature (Gustin et al, 1997;Sarkis and Sundarraj, 2000) include:…”
Section: Internal Systems and Software Requirementsmentioning
confidence: 99%